Profile of the University of the Philippines Center for Integrative and Development Studies (UPCIDS) libraries with focus on collection management - Loria, Mary Rose V.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study aims to provide a profile of the University of the Philippines Center for Integrative and Development Studies libraries. It particularly discussed their current collection management practices and their respective strengths and weaknesses. The descriptive method of research was used to conduct the study. Data were gathered from the librarians thru structured questionnaire and interview schedule. The study was conducted during the first semester of the school year 1998-1999.
The findings showed that the UPCIDS library has a collection which is relevant to the objectives of the Center. However, the collection management practices are affected by several factors: the Executive Committee, staff, budget, and the absence of a written collection management policy. The findings also showed that the Psychosocial Trauma Library has a small collection of materials relevant to the program. Likewise, the efficient collection management of the library is hindered by factors such as budget, staff, and the absence of a written collection management policy.
This study recommends that there must be proper representation of both users and the UPCIDS staff in the Executive Committee; a regular budget should be provided to realize collection development; the library staff should attend seminars, etc. to familiarize themselves with the goals of the Center; practicum students from library schools can also aid in the technical tasks of the library; continuous acquisition of relevant materials, formulation of a written collection management policy to define the procedures and policies involving the collection; conservation thru multiple copies to maximize the budget allocated; and resource sharing to help enrich resources.
Similar recommendations are suggested to the PST library: a regular library budget must be provided, hiring of additional staff, continuous acquisition of relevant materials, drafting of a written collection management policy, regular practice of preserving and conserving the materials in the collection, engaging in interlibrary resource sharing to keep up with the growing demand for information, use of a client-centered analysis of the collection, acquisition of additional computer units to hasten the automation of the library, and space expansion is also advised to accommodate the growing collection and the growing number of clients.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Collection management (Libraries) -- Philippines -- Quezon City; University of the Philippines Center for Integrative Development Studies (UPCIDS).